Constructivism Based Learning: Design and Practice - Lia Kurniawati; Abdul Muin; Ramdani Miftah (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2015)
Abstract One of many problems in the madrasahs is that learning processes less-involve students actively (teacher-centered), thus, it affects to the improvement of learning outcomes and quality of the graduates. The purposes of this study are , firstly, to analyze what type of constructivism learning models, which can be developed to overcome madrasahs’ problems. Secondly, how to design and implement a learning plan based on the developed constructivism models. This research was conducted at Private Islamic Elementary School (Madrasah) Ad-Diyanah Ciputat, South Tangerang. Research method used in this study is descriptive-qualitative research. The results showed that the active learning models based on constructivism are suitable to be developed in the Madarasah, which were the models of Problem Based Learning (PBM), Realistic Learning, Inquiry Learning and Thematic Learning and also how the development of the learning processes from the lesson plans to the learning implementation showed a paradigm shifting from teacher-centered to student-centered. Abstrak Salah satu permasalahan di madrasah-madrasah adalah proses pembelajaran yang kurang melibatkan siswa secara aktif (berpusat pada guru), sehingga hal ini mengakibatkan pada peningkatan hasil belajar dan kualitas lulusan. Tujuan dari penelitian ini adalah, pertama, untuk menganalisis jenis model pembelajaran konstruktivisme apa yang dapat dikembangkan untuk mengatasi permasalahan di madrasah. Ke dua, bagaimana merancang dan melaksanakan rencana pembelajaran berdasarkan model konstruktivisme yang dikembangkan. Penelitian ini dilaksanakan di Sekolah Dasar Swasta (madrasah) Ad-Diayanah Ciputat, Tangerang Selatan. Metode penelitian yang digunakan adalah metode deskriptif-kualitatif. Hasil penelitian menunjukkan bahwa model pembelajaran aktif yang berbasis konstruktivisme sesuai untuk dikembangkan di madrasah, yakni model pembelajaran Problem Based Learning (PBL), Pembelajaran Realistis, Pembelajaran Inkuiri dan Pembelajaran Tematik, juga bagaimana pengembangan proses pembelajaran dari rencana pembelajaran ke pelaksanaan pembelajaran menunjukkan perubahan paradigma dari berpusat-pada-guru menjadi berpusat-pada-siswa. How to Cite : Kurniawati, L. Muin, A. Miftah, R., M. (2015). Constructivism Based Learning: Design and Practice. TARBIYA: Journal Of Education In Muslim Society, 2(2), 123-130. doi:10.15408/tjems.v2i2. 3183. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i2.3183